THE RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDES REGARDING THE DANGERS OF FREE SEX IN JUNIOR HIGH SCHOOL STUDENTS - Zubaeda; Ratna Sari Rumakey; Asih Dewi Astuti (Medika Alkhairaat: Jurnal Penelitian Kedokteran dan Kesehatan, 2023)
Adolescence is a period of development that is very critical among other periods because at this time there is a transition from childhood to adulthood. Low knowledge will affect the attitude of adolescents in attitudes about free sex accompanied by the strong influence of peers at adolescence, making adolescents have unhealthy sexual acts. The purpose of this study was to determine the relationship between the level of knowledge and student attitudes about the dangers of free sex in class VIII students at SMP Negeri 2 Kairatu. The research design used cross sectional. The sample in this study amounted to 78 respondents with a total sampling approach. The analysis of this study uses the Spearman Rho test. The results of the study stated that there was a significant relationship between knowledge and student attitudes about the dangers of free sex, (p-value 0.001). This study concluded that there was a relationship between the level of knowledge and student attitudes about the dangers of free sex in class VIII students at SMP Negeri 2 Kairatu. It is hoped that the results of this study can be a reference for schools to provide more counseling guidance about the dangers of free sex to students.